BENTUK CAMPUR KODE BAHASA PROKEM PADA TUTURAN BERBAHASA INDONESIA DALAM NOVEL SENIOR KARYA EKO IVANO WINATA - Supriyati Supriyati; Pangesti Kartika Putri (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this research is to describe code mixing of prokem language towards Indonesian language in the novel Senior by Eko Ivano Winata”. From this novel, it can be found that there is code mixing in a form of words, phrases, and clauses which become the object of the research. This research is descriptive qualitative. The data is taken from the utterances in the novel Senior by Eko Ivano Winata. The dource of the data is the novel Senior by Eko Ivano Winata. The analysis of the data is done by several steps: collecting all of data, choosing the data, interpreting the data logically, and making a conclusion towards each data. Based on the result of the analysis, it can be concluded that the form of code mixing in the novel Senior by Eko Ivano Winata is code mixing in the form of word such as  lu, gue, and enggak. Code mixing in the form of clause is  diem enggak and sampe lu. Moreover, Code mixing in the form of clause is gue denger lu, gue enggak, and lu enggak.Keywords: Code Mixing, Prokem language, Novel